Evaluation of engineering, physiochemical and nutritional properties of three different varieties of pomelo fruit - Simple Sharma; Barinderjit Singh; Yashi Srivastava (Journal of Horticulture and Postharvest Research)
Purpose: The aim of this study was to identify the engineering, physiochemical, and nutritional properties of selected varieties of pomelo fruit. Research method: The study was carried out using a one-way analysis of variance with three replications on selected varieties of pomelo fruit. The experiment consisted of three cultivars, namely red, pink, and white pomelo to analyze the engineering, physiochemical, and nutritional properties. Findings: The results revealed that the geometrical and gravimetric analysis showed variation among different parameters of varieties of pomelo fruit. Textural property, such as the puncture resistance test was highest for the pink variety at 20.19 N. The color analysis in the optical parameter showed the highest values for the white variety of pomelo. The identification of functional compounds done by Fourier transform infrared spectroscopy provides advancement for the production of different functional products. The assessment of physicochemical and nutritional properties provides knowledge of nutrients, essential minerals (boron, magnesium, aluminum, silicon, phosphorous, potassium, iron, copper, zinc), and quality of fruit, making it an expert functional food ingredient and can be utilized for various applications in food industries. The physicochemical and nutritional properties indicated significant variation (p<0.05) among different parts of selected varieties of pomelo fruit. Research limitations: There was no limitation. Originality/Value: Pomelo is an underutilized fruit with a rich source of bioactive compounds, has a favorable nutritional profile, and has health-improving effects. With its great nutritive value, utilization of this fruit is still very limited because of a lack of information regarding its physicochemical, nutritional, and processing technologies. This research work on different food properties provides a broad area of knowledge regarding designing, processing, storage, transportation, product development and is useful to encourage commercialization.